The ultimate Disney party book - Ward, Jessica (Disney Party., 2015)
The Ultimate Disney Party Book is your perfect partner when throwing a party. Whether it s a birthday party, baby shower, celebration of a milestone or just a great bbq with friends and family, this book is your perfect partner in crime. The book is divided into chapters based on a theme for your party and in each chapter you can find great recipes for cakes and other dishes, perfect decorations ideas, fun invitations and the best games to play.